2012
DOI: 10.2478/s11756-012-0056-3
|View full text |Cite
|
Sign up to set email alerts
|

In-fusion expression and characterization of β-xylanase and β-1,3-1,4-glucanase in Pichia pastoris

Abstract: Two chimeric genes, XynA-Bs-Glu-1 and XynA-Bs-Glu-2, encoding Aspergillus sulphureus β-xylanase (XynA, 26 kDa) and Bacillus subtilis β-1,3-1,4-glucanase (Bs-Glu, 30 kDa), were constructed via in-fusion by different linkers and expressed successfully in Pichia pastoris. The fusion protein (50 kDa) exhibited both β-xylanase and β-1,3-1,4-glucanase activities. Compared with parental enzymes, the moiety activities were decreased in fermentation supernatants. Parental XynA and Bs-Glu were superior to corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Accordingly, access to solvent for long (average length of 21.0 ± 7.6 residues), medium (9.1 ± 2.4) and short (4.5 ± 0.7) linkers are about 42.5, 26.3 and 14.4%, respectively (Chen et al 2013;George and Heringa 2003). Although a linker should be long enough so that each enzyme acts independently, the possibility of breakage increases if the linker be too long (Qiao and Cao 2012). It has been demonstrated that a 31 amino acids linker is suitable not only to prevent collision of two enzymes, but also to make great flexibility to provide free access and binding to the substrate (Diogo et al 2015).…”
Section: End To End Fusion; Simple and Prevalent Methodsmentioning
confidence: 99%
“…Accordingly, access to solvent for long (average length of 21.0 ± 7.6 residues), medium (9.1 ± 2.4) and short (4.5 ± 0.7) linkers are about 42.5, 26.3 and 14.4%, respectively (Chen et al 2013;George and Heringa 2003). Although a linker should be long enough so that each enzyme acts independently, the possibility of breakage increases if the linker be too long (Qiao and Cao 2012). It has been demonstrated that a 31 amino acids linker is suitable not only to prevent collision of two enzymes, but also to make great flexibility to provide free access and binding to the substrate (Diogo et al 2015).…”
Section: End To End Fusion; Simple and Prevalent Methodsmentioning
confidence: 99%